2001
DOI: 10.1038/sj.onc.1204380
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of AP-1 subunits in skin physiology and pathology

Abstract: The mouse skin has become the model of choice to study the regulation and function of AP-1 subunits in many physiological and pathological processes in vivo and in vitro. Genetically modi®ed mice, in vitro reconstituted skin equivalents and epidermal cell lines were established, in which AP-1-regulated genetic programs of cell proliferation, di erentiation and tumorigenesis can be analysed. Since the epidermis, as our interface with the environment, is subjected to radiation and injury, signal transduction pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
326
3
24

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(375 citation statements)
references
References 116 publications
(103 reference statements)
22
326
3
24
Order By: Relevance
“…Investigation of the molecular mechanism of carcinoma cell differentiation/ dedifferentiation is a momentous subject in cancer cell biology and may contribute to the development of a novel strategy to relieve patient suffering from the disease. Although investigators reported that various factors are involved in carcinoma cell differentiation and dedifferentiation, accumulating evidence implies that transcriptional misregulation takes a critical part in the events (Angel et al, 1996;Hunter, 1997;Visvader et al, 1997;Battle et al, 2000;Cano et al, 2000). In the present study, our data demonstrate for the first time that LMO4 and LDB1 form protein complexes in the nucleus and are expressed in carcinoma cells at the invasive front, and their immunoreactivity is increased in lessdifferentiated carcinomas and in metastasised lymph nodes.…”
Section: Discussionsupporting
confidence: 59%
“…Investigation of the molecular mechanism of carcinoma cell differentiation/ dedifferentiation is a momentous subject in cancer cell biology and may contribute to the development of a novel strategy to relieve patient suffering from the disease. Although investigators reported that various factors are involved in carcinoma cell differentiation and dedifferentiation, accumulating evidence implies that transcriptional misregulation takes a critical part in the events (Angel et al, 1996;Hunter, 1997;Visvader et al, 1997;Battle et al, 2000;Cano et al, 2000). In the present study, our data demonstrate for the first time that LMO4 and LDB1 form protein complexes in the nucleus and are expressed in carcinoma cells at the invasive front, and their immunoreactivity is increased in lessdifferentiated carcinomas and in metastasised lymph nodes.…”
Section: Discussionsupporting
confidence: 59%
“…AP-1 target genes are differentially regulated by distinct AP-1 dimers. The dynamic changes in Jun and Fos composition after stress-stimuli balance discrete signals that play a key role in defining whether cells undergo apoptosis, survival or senescence (4). Many compounds can induce apoptosis in tumor cells by interfering with AP-1.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Potentially, therefore, activated c-Jun could play an important role in stromal-epithelial interactions. 20,23 The Jun-family of proteins function as critical transcription factors, regulating the expression of many genes such as IGFs, fibroblast growth factors, epithelial growth factor, hepatocyte growth factor, and transforming growth factor-␤. It is not surprising then that they may also regulate downstream paracrine effectors between stromal and epithelial cells.…”
mentioning
confidence: 99%